Minimal oligosaccharide structures required for induction of immune responses against meningococcal immunotype L1, L2, and L3,7,9 lipopolysaccharides determined by using synthetic oligosaccharide-protein conjugates. - Verheul, A F (1991)
The 12 types of meningococcal lipopolysaccharide (LPS) (immunotypes) contain immunotype-specific and cross-reactive epitopes situated on the oligosaccharide part of the LPS molecules. To identify useful cross-reactive epitopes and to determine minimal oligosaccharide structures required for the induction of an immune response against the most prevalent immunotypes, L1, L2, and L3,7,9, synthetic as well as native LPS-derived oligosaccharides were conjugated with tetanus toxoid. L3,7,9 phosphoethanolamine (PEA) group-containing oligosaccharide-tetanus toxoid conjugates evoked high immunoglobulin G (IgG) antibody levels in rabbits which were detected by an L2-, L3,7,9-, and, depending on the antiserum, L1-specific enzyme-linked immunosorbent assay (ELISA). Inhibition studies revealed that an identical antibody population was detected by L1 and L3,7,9 ELISA, indicating a similar tertiary structure of the inner core oligosaccharide of these two immunotypes. These antibodies recognize PEA group-containing epitopes present on the L1 and L3,7,9 LPS. An L2 PEA group-containing oligosaccharide-tetanus toxoid conjugate elicited L2- and L3,7,9-specific IgG antibodies, but in contrast with the L3,7,9 conjugates, no L1-specific IgG antibodies were evoked. These results indicate that L1 and L2 LPS do not contain cross-reactive epitopes, whereas both L2 and L3,7,9 LPS and L1 and L3,7,9 LPS possess common determinants. Three linear oligosaccharides and one branched oligosaccharide, representing partial structures of the inner core oligosacchardes of meningococcal LPS, were synthesized. Only the branched synthetic oligosaccharide-containing conjugate was able to induce and L1- and L3,7,9-specific immune response, whereas the linear oligosaccharide-protein conjugates evoked L2-specific immune responses. The branched oligosaccharide (beta-D-Glcp(1----4)-[L-alpha-D-Hepp(1----3)]-L-alpha-D-Hepp ) is therefore considered a minimal structure required for the induction of an immune response against L1 and L3,7,9 LPS and part of a cross-reactive epitope between these two immunotypes. For L2-specific immune responses, oligosaccharide structures terminating in beta-D-Glcp(1----4), alpha-D-GlcNAcp(1----2), or L-alpha-D-Hepp(1----5) are needed. The results suggest that it is possible to prepare an oligosaccharide structure with the ability to evoke an immune response against L1, L2, and L3,7,9 LPS. A feasible structure for such a "hybrid" oligosaccharide is discussed.